Perancangan BackEnd Sepekan Inventaris dengan Framework Laravel di PT Pundi Mas Berjaya - Stefanus Eko Prasetyo; Steven Lie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
PT. Pundi Mas Berjaya is one of the solution providers engaged in software. The company, which was established in 2014, has designed, developed and used many solutions in the fields of transportation, education, food delivery, freight forwarding and ecommerce. PT. Pundi Mas Berjaya needs a system that can control office equipment and supplies to be more systemized so as to minimize the risk of loss of goods. Therefore, the inventory website system with the name Sepekan was designed with the aim of making it easier for users to control their equipment and equipment. in the project, I as the BackEnd make programming logic so that the functions of the application work as desired by the related party. There are several software used to help his work, namely using the larvavel framework by using php and MYSQL languages created in visual studio code. Keywords: Sepekan, Inventory, Laravel, MYSQL,